Comparison of Frequency of Rapid Virological Response in Patients of Hepatitis C being Treated with 25-OH Vitamin D along with Sofosbuvir/Ribavirin with Those Treated with Sofosbuvir/Ribavirin only - Jamila Khan, Noreen Adil, Aqsa Naseer, Muhammad Asif, Asma Sabir, Sadia Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatitis C is the leading cause of liver damage that lead to death if left untreated. Sofosbuvir has recently attained enormous success due to high rate of virological response. Recent studies have shown that addition of vitamin D to antiviral therapy improves the efficacy of treatment in patients with Hepatitis C. Objective: To compare the frequency of virological response in hepatitis C patients treated with vitamin D along with sofosbuvir plus ribavirin to those treated with sofosbuvir plus ribavirin only Study Design: Randomized-controlled-trial Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital, Rawalpindi from 1st November 2017 to 30th April 2018. Methodology: One hundred patients of chronic hepatitis C were included. Patients were randomly divided into two groups; group A receiving vitamin D along with sofosbuvir plus ribavirin and group B receiving sofosbuvir plus ribavirin therapy only. Patients were treated for 6 months and their RVR was monitored. Results: The mean age of patients in combination group was 39.0±12.92 years and in control group were 36.66±13.80years. After 4 weeks, RVR (no HCV RNA detected on PCR) was achieved in 31 (62%) cases in combination group while in 19 (38%) cases there was still HCV RNA present. In control group, RVR could be achieved in 18 (36%) cases while in 32 (64%) cases, RVR could not be achieved. The difference was significant between both groups (p<0.05). Conclusion: The addition of vitamin D can help in achieving RVR in >50% cases within 4 weeks. So addition of vitamin D in standard therapy may help to improve the quality of treatment.